MoTe2 Photodetector for Integrated Lithium Niobate Photonics - Qiaonan Dong; Xinxing Sun; Lang Gao; Yong Zheng; Rongbo Wu; Ya Cheng (Nanomaterials, 2025)
The integration of a photodetector that converts optical signals into electrical signals is essential for scalable integrated lithium niobate photonics. Two-dimensional materials provide a potential high-efficiency on-chip detection capability. Here, we demonstrate an efficient on-chip photodetector based on a few layers of MoTe2 on a thin film lithium niobate waveguide and integrate it with a microresonator operating in an optical telecommunication band. The lithium-niobate-on-insulator waveguides and micro-ring resonator are fabricated using the femtosecond laser photolithography-assisted chemical–mechanical etching method. The lithium niobate waveguide-integrated MoTe2 presents an absorption coefficient of 72% and a transmission loss of 0.27 dB µm−1 at 1550 nm. The on-chip photodetector exhibits a responsivity of 1 mA W−1 at a bias voltage of 20 V, a low dark current of 1.6 nA, and a photo–dark current ratio of 108 W−1. Due to effective waveguide coupling and interaction with MoTe2, the generated photocurrent is approximately 160 times higher than that of free-space light irradiation. Furthermore, we demonstrate a wavelength-selective photonic device by integrating the photodetector and micro-ring resonator with a quality factor of 104 on the same chip, suggesting potential applications in the field of on-chip spectrometers and biosensors.